2012
DOI: 10.1111/j.1745-6584.2012.01014.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Radial Flow in Synthetic Flow Systems

Abstract: Traditional analysis methods used to determine hydraulic properties from pumping tests work well in many porous media aquifers, but they often do not work in heterogeneous and fractured-rock aquifers, producing non-plausible and erroneous results. The generalized radial flow model developed by Barker (1988) can reveal information about heterogeneity characteristics and aquifer geometry from pumping test data by way of a flow dimension parameter. The physical meaning of non-integer flow dimensions has long been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Well test interpretation can be improved by analyzing the second drawdown derivative response over time, referred to as the flow dimension, n . This concept, introduced by Barker (), is related to the power by which the cross‐sectional flow change with distance from the borehole (Bowman et al ), and therefore is an additional tool to identify transient flow patterns during the test.…”
Section: Field Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Well test interpretation can be improved by analyzing the second drawdown derivative response over time, referred to as the flow dimension, n . This concept, introduced by Barker (), is related to the power by which the cross‐sectional flow change with distance from the borehole (Bowman et al ), and therefore is an additional tool to identify transient flow patterns during the test.…”
Section: Field Examplesmentioning
confidence: 99%
“…If a stable flow dimension exits, the second derivative will exhibit a constant value (preferably for one log cycle of time), equivalent to n ; otherwise, no stable flow dimensions occur, and no unique hydraulic properties can be inferred analytically from the test. The flow dimension is defined for values between zero to three, such as n = 0, for closed aquifers, n = 1 for linear flow, n = 2 for radial flow, n = 3, for spherical flow and values between these integer dimensions for highly heterogeneous media (Beauheim et al ; Giese et al ) or nonfractal geometries (Bowman et al ).…”
Section: Field Examplesmentioning
confidence: 99%
“…Translation of scalings in terms of generalized non-integral hydraulic dimensions has proven informative but challenging (e.g., Doe, 1991;Le Borgne et al, 2004;Bernard et al, 2006;Cello et al, 2009;Rafini and Larocque, 2009;Odling et al, 2013;Giese et al, 2017;Ferroud et al, 2018). Nonstandard pres-sure responses may be observed in complex reservoir geometries, which can be fractal-like structures (e.g., Chang and Yortsos, 1990;Acuna and Yortsos, 1995;Lods and Gouze, 2008) or non-fractal structures (e.g., Jourde et al, 2002b;Bowman II et al, 2013). Other studies have shown that fractional flow can be developed in some 2D heterogeneous transmissivity fields, such as long-range correlated media (e.g., Walker et al, 2006;de Dreuzy and Davy, 2007).…”
mentioning
confidence: 99%